Wine Traceability and Counterfeit Reduction: Blockchain-based Application for a Wine Supply Chain - Tokkozhina, U.; Martins, A.; Ferreira, J. (EAI INTSYS 2021 - 5th EAI International Conference on Intelligent Transport Systems, 2021)
With the growing number of counterfeits in food supplier chains, one of the most important subjects to a final consumer is the assurance of product le-gitimacy and safety to consume. In this paper, we develop an approach to-wards wine traceability, with main objectives on combating counterfeit and increasing brand reputation by assuring the origin of wine to the final consumer. We build an architecture for a blockchain-based system to track and record all the main transactions between the supply chain participants from the moment the grapes are harvested until the moment when the final consumer is making a decision to purchase the wine. This application shows the enormous potential of blockchain technology to reduce counterfeiting levels and assure the final consumer with the origin of the wine, potentially avoiding health risks that counterfeit wine can cause, and thus increasing the wine brand reputation.